Isolated Spontaneous Renal Artery Dissection Presented with Flank Pain - Shruti P. Gandhi; Kajal Patel; Bipin C. Pal (Case Reports in Radiology)
Spontaneous renal artery dissection is a rare but important cause of flank pain. We report a case of isolated spontaneous renal artery dissection in 56-year-old man complicated by renal infarction presented with flank pain. Doppler study pointed towards vascular pathology. Computed tomography (CT) angiography was used to make final diagnosis which demonstrated intimal flap in main renal artery with renal infarction.